Perinatal Exposure to Bisphenol A or Diethylstilbestrol Increases the Susceptibility to Develop Mammary Gland Lesions After Estrogen Replacement Therapy in Middle-Aged Rats - Gomez, Ayelen; Delconte, Melisa; Altamirano, Gabriela; Vigezzi, Lucia; Bosquiazzo, Veronica; Barbisan, Luís [UNESP]; Ramos, Jorge; Luque, Enrique; Muñoz-de-Toro, Mónica; Kass, Laura (Springer Nature, 2017)
The development of the mammary gland is a hormone-regulated event. Several factors can dysregulate its growth and make the gland more susceptible to cellular transformation. Among these factors, perinatal exposure to xenoestrogens and hormone replacement therapy has been associated with increased risk of developing breast cancer. Here, we assessed the effects induced by estrogen replacement therapy (ERT) in ovariectomized (OVX) middle-aged rats and whether perinatal exposure to diethylstilbestrol (DES) or bisphenol A (BPA) modified these effects in the mammary gland. Pregnant rats were orally exposed to vehicle, 5 μg DES/kg/day, or 0.5 or 50 μg BPA/kg/day from gestational day 9 until weaning. Then, 12-month-old offspring were OVX and treated with 17β-estradiol for 3 months. Morphological changes and the percentage of epithelial cells that proliferated or expressed estrogen receptor alpha (ESR1) and progesterone receptor (PR) were analyzed in mammary gland samples of 15-month-old animals. ERT induced lobuloalveolar hyperplasia and ductal cysts in the mammary gland of middle-aged rats, associated with a higher proliferation index of epithelial cells. Perinatal exposure to DES followed by ERT increased the number of cysts and induced the formation of fibroadenoma and ductal carcinoma in situ, without modifying the expression of ESR1 or PR. Also, after 3 months of ERT, BPA-exposed rats had a higher incidence of ductal hyperplasia and atypical lobular hyperplasia than animals under ERT alone. In conclusion, perinatal exposure to xenoestrogens increases the susceptibility of the mammary gland to develop cysts and hyperplastic lesions when confronted with ERT later in life.
Keywords: Bisphenol A; Diethylstilbestrol; Endocrine disruptor; Estrogen replacement therapy; Mammary gland